Molecular surveillance of small ruminant anaplasmosis and phylogenetic investigations on zoonotic Anaplasma capra from distinct agro-ecological regions of Pakistan - Azam, M.N.; Atif, F.A.; Kashif, M.; Zaman, M.A.; Imran, M. (Polish Journal of Veterinary Sciences, 2026)
Anaplasma infects diverse cell types in animals and humans, worldwide. The current study was aimed at evaluating the occurrence, risk parameters and phylogeny of Anaplasma capra in small ruminants from three agro-climatically distinct regions of Pakistan. A total of 600 blood samples were randomly gathered from asymptomatic sheep and goats from Toba Tek Singh, Khushab, and Dera Ismail Khan districts of Pakistan using a multistage cluster sampling technique from January 2023 to May 2024. The blood samples were analyzed for Anaplasma infection targeting the 16S rRNA gene using the PCR followed by sequencing. A pre-tested questionnaire was used utilized to gather information regarding risk factors. The prevalence of anaplasmosis was revealed as 27.83% (167/600). The data suggested a higher frequency of disease in goats (30.37%) compared to sheep (24.82%). Analysis of multivariate logistic regression determined that cracks in walls (p<0.0001, OR=2.240, CI=1.439-3.487) and grooming practice (p<0.01, OR=1.793, CI=1.235-2.604) were the significant risk factors. The phylogeny of the 16S rRNA gene identified two separate clusters of A. capra exhibiting 99-100% similarity with various geographic isolates. The isolates of the current study exhibited higher homology with isolates from France, Ghana, South Korea, Turkey, China, and Pakistan traced from ticks, sheep, water buffalo, cattle, and water deer, respectively. In conclusion, anaplasmosis is widespread in the study regions with indication of genetic diversity. Additional research is required on the clinicopathological and potential vectors of zoonotic A. capra for devising better treatment and control measures.